My Mom’s Letter - Robert M. Randolph (Journal of the Assembly for Expanded Perspectives on Learning, 2016)
A longtime poet explains how a letter from his mother reminds him that regardless of our language skills and backgrounds, our writing can still bear witness to the values and ethics that guide our lives.